2007
DOI: 10.1002/aic.11373
|View full text |Cite
|
Sign up to set email alerts
|

Reaction monitoring of the MMA polymerization at marginal dispersion stability

Abstract: in Wiley InterScience (www.interscience.wiley.com).The free-radical dispersion polymerization of methyl methacrylate was studied using the reaction calorimetry technique. An especially developed calorimeter for use with supercritical fluids was employed and a set of experiments was explicitly designed to isolate the effect of the pressure. It was found that, under marginal dispersion stability conditions, small pressure changes can have significant effects on the reaction evolution. The pressure was also found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Additional results on the monitoring of the model reaction under the reference conditions regard an observed small deceleration at approximately 24 min. It was previously shown that the reference conditions are at the limit of the dispersion stability and that a small increase in the reactant concentrations can improve this stability and lead to the disappearance of the deceleration . In this study the role of stirring was also investigated under these unstable conditions, given that previous reports have shown that intensive mixing can either improve or worsen the reaction conditions. , The results of this investigation are presented in Figure .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additional results on the monitoring of the model reaction under the reference conditions regard an observed small deceleration at approximately 24 min. It was previously shown that the reference conditions are at the limit of the dispersion stability and that a small increase in the reactant concentrations can improve this stability and lead to the disappearance of the deceleration . In this study the role of stirring was also investigated under these unstable conditions, given that previous reports have shown that intensive mixing can either improve or worsen the reaction conditions. , The results of this investigation are presented in Figure .…”
Section: Resultsmentioning
confidence: 95%
“…First, there is significant experience in this reaction both theoretical and experimental and both in organic solvents and in scCO 2 . Second, this reaction is probably the most studied free-radical dispersion polymerization in scCO 2 in the literature, which allows for comparing the results of this study with previous reports. , The reaction conditions were set so that the initial reaction mixture is homogeneous and that the continuous phase can efficiently solubilize the stabilizer molecules in order to form a stable polymer particle dispersion. The latter has been previously shown to affect dramatically the evolution of the polymerization …”
Section: Methodsmentioning
confidence: 99%
“…It has been previously shown that as far as the stabilizer mass (wt.% with respect to the monomer), the CO 2 mass, the pressure and the stirring speed are concerned, there are limits below which the stability of the formed dispersion is compromised, resulting in a dramatic decrease of the reaction rate and in significant agglomeration and coalescence of the formed polymer particles [9, 11]. The conditions of the base case were found to be at the limit of the dispersion stability.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl methacrylate (MMA) as a very important chemical feedstock is widely used in the field of optical elements, aviation units, optical fibers, optical mirrors, robots, and transistor fabrication. Meanwhile, methylacrolein (MAL) is the key stock for synthesis of MMA through selective oxidation followed by esterification or direct oxidative esterification with methanol. Until now, the approaches to MAL are mainly focused on selective oxidation of isobutene or isobutane and sec -amine-catalyzed Mannich reactions between propanal and formaldehyde, which are summarized in Scheme .…”
Section: Introductionmentioning
confidence: 99%